Internal Factors Influencing Rural Ecotourism Entrepreneurship (Case Study in Bogor Regency of West Java) - Purba, Indra Setiawan; Avenzora, Ricky; Anggraini, Eva; Darusman, Dudung (Universitas Negeri Semarang, 2023)
To Developing rural ecotourism business requires actors with good entrepreneurial capacity. The factors that cause the formation of entrepenership in individuals of ecotourism villages in Indonesia are not yet known. This study aimed to analyze examine the internal factors that build entrepreneurial capacity in rural ecotourism. The research location was in four tourism villages in Bogor Regency, namely Ciasihan, Sirnajaya, Watesjaya and Pabuaran Villages Individuals who manage natural resources, innovate and take risks in running their business are entrepreneurs and vice versa.The number of respondents was 442. This number is calculated from four selected villages in Bogor regency where sampling uses purposive sampling which were divided into two groups, namely the entrepreneurial group of 240 respondents and the non-entrepreneurial group of 202 respondents . Primary data were obtained through filling out a list of questions by respondents using a closed-ended questionnaire by applying “the one score one indicator scoring system pattern”. Data analysis was carried out in a quantitative descriptive manner based on the average value of each indicator . To know the variables that have a significant effect on rural ecotourism entrepreneurship needed an analysis of the quality relationship between variables carried out using logistic regression analysis.The results showed that the significant variables that influenced rural ecotourism entrepreneurship are: 1) openness, 2) achievement motivation, 3) closed mindset, 4) innovative 5) efficient, 6) open mindset, and 7) locus of control. A qualitative approach is carried out by entering rural communities with observations and interviews, to find out the behavior and internal variables that exist in individual rural communities that form entrepreneurship.The largest Odds Ratio value was on the openness variable with a score of 3.242, which meant that if individuals in tourist villages had an openness attitude, they would tend to have entrepreneurship 3.242 times higher than those who did not have an openness attitude. Entrepreneurship in tourist villages is very important to create ecotourism businesses that can change rural resources into added value. Rural communities need to be understood fromtheir individual behavior as forming businesses in the field of rural ecotourism.